Jeux d’acteurs et fragilisation de l’agriculture périurbaine dans l’agglomération d’Oran (Algérie) - Madina Asmaa Missoumi; Mohamed Hadeid; Dider Desponds (Études Caribéennes)
The capital of western Algeria, Oran, has experienced a particularly strong rate of urbanization for several decades under the massive urban pressure. The result is a gradual urban sprawl on agricultural land through. Therefore, satellite images have been used to monitor and quantify urban sprawl over a period of 30 years (1987-2017). The results are confirmed by an in-situ investigations conducted with the actors involved in these transformations. It reveals various practices of misappropriation of agricultural lands due to the uncontrolled application of housing and equipment programs. This decline in agricultural areas is evolving at an alarming rate, agricultural lands being gradually replaced by urban extensions, regardless whether they have been the purpose of planning or the result of illicit constructions. This accelerated consumption of agricultural land is taking place despite some talks claiming to protect it. The danger of suburban agriculture is a major challenge for the agglomeration of Oran, which is to be apprehended according to complementary approaches, quantitative and qualitative.